PENGARUH AKTIVITAS ANTROPOGENIK TERHADAP BOD (BIOLOGICAL OXYGEN DEMAND) DI SUNGAI BADENG BANYUWANGI - Nadila; Kurnia, Tristi Indah Dwi (JURNAL BIOSENSE, 2025)
This research aims to study how human activities affect the biological oxygen demand (BOD) values in the Badeng River, Banyuwangi. These rivers are important resources that support household needs and economic activities in the surrounding area. The use of pesticides and agricultural fertilizers, as well as industrial and livestock waste, and the disposal of domestic waste, are suspected to contribute to the increase in BOD levels, indicating a decline in water quality. The research measures BOD values through laboratory analysis using iodometric titration. To examine the impact of human activities on water quality, water samples were taken from the upstream and downstream sections of the river. The research results show that the BOD value in the downstream section is higher (1.49 mg/L) compared to the upstream section (1.29 mg/L), but both are still below the threshold of class II water quality standards (3 mg/L). This indicates that the increase in BOD values downstream of the river is influenced by human activities. Therefore, better management of human activities is necessary to maintain the sustainability of the ecosystem and the quality of the river water.